2015
DOI: 10.1007/s40429-015-0046-y
|View full text |Cite
|
Sign up to set email alerts
|

Endophenotypes for Alcohol Use Disorder: An Update on the Field

Abstract: The endophenotype concept was first proposed as a strategy to use (purportedly) genetically simpler phenotypes in gene identification studies for psychiatric disorders, and is distinct from the closely related concept of intermediate phenotypes. In the area of alcohol use disorder (AUD) research, two candidate endophenotypes have produced replicable genetic associations: level of response to alcohol and neurophysiology markers (e.g., event-related oscillations and event-related potentials). Additional candidat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
44
0
2

Year Published

2016
2016
2020
2020

Publication Types

Select...
6
3
1

Relationship

1
9

Authors

Journals

citations
Cited by 50 publications
(50 citation statements)
references
References 161 publications
4
44
0
2
Order By: Relevance
“…In light of the current findings, future investigations of AUP focusing on neurochemical systems and networks involved in the neurobiology of sensation seeking may be especially compelling. However, enthusiasm over the endophenotype approach should also be tempered given that certain candidate endophenotypes may not be any "genetically simpler" than the psychiatric outcomes they are associated with (Salvatore et al, 2015). We await future genetically informed investigations that may shed light on other important neurobiological pathways and mechanisms underlying the risk for AUP that have yet to be uncovered.…”
Section: Discussionmentioning
confidence: 99%
“…In light of the current findings, future investigations of AUP focusing on neurochemical systems and networks involved in the neurobiology of sensation seeking may be especially compelling. However, enthusiasm over the endophenotype approach should also be tempered given that certain candidate endophenotypes may not be any "genetically simpler" than the psychiatric outcomes they are associated with (Salvatore et al, 2015). We await future genetically informed investigations that may shed light on other important neurobiological pathways and mechanisms underlying the risk for AUP that have yet to be uncovered.…”
Section: Discussionmentioning
confidence: 99%
“…A long tradition of research has demonstrated reduction of the parietal target/ oddball P3 ERP in relation to various forms of SUDs, including alcohol, nicotine, and illicit drug use (Anokhin et al, 2000;Costa et al, 2000;Iacono, Carlson, Malone, & McGue, 2002;Patrick et al, 2006;Perlman, Markin, & Iacono, 2013;Porjesz et al, 1998; for a review, see Euser et al, 2012). Evidence from twin and family studies strongly supports the interpretation that P3 amplitude reduction (P3AR) indexes a substance use (Euser et al, 2012;Iacono & Malone, 2011;Porjesz et al, 2005;Salvatore et al, 2015).…”
Section: Introductionmentioning
confidence: 98%
“…Many thoughtful endophenotype articles populate the literature (for recent examples, see Anokhin, 2014; Beauchaine, 2009; Burton et al, 2015; Campanella, Pogarell, & Boutros, 2014; Euser et al, 2012; Faraone, Bonvicini, & Scassellati, 2014; Ferrarelli, 2013; Glahn et al, 2014; Goldstein & Klein, 2014; W. G. Iacono & Malone, 2011; Lenzenweger, 2013; Loo, Lenartowicz, & Makeig, 2015; Manoach & Agam, 2013; Miller & Rockstroh, 2013; Moses-Kolko, Horner, Phillips, Hipwell, & Swain, 2014; Owens, Bachman, Glahn, & Bearden, 2016; Pearlson, 2015; Rosen, Spellman, & Gordon, 2015; Rubenstein, Wiggins, & Lee, 2015; Salvatore, Gottesman, & Dick, 2015; Swerdlow, Gur, & Braff, 2015), and many of these share a conviction that endophenotypes are valuable for identifying genetic liability . However, despite their introduction to psychiatry by Gottesman and Shields (I.…”
Section: 0 Introductionmentioning
confidence: 99%